Amorphophallus konjac: traditional uses, bioactive potential, and emerging health applications - Jain, Archana; Sarsaiya, Surendra; Gong, Qihai; Wu, Qin; Shi, Jingshan (Frontiers in Plant Science, 2025)
Amorphophallus konjac is a perennial plant native to Southeast Asia, renowned for its edible corms and rich nutritional value. The bioactive component, konjac glucomannan (KGM), has garnered significant attention due to its broad applications. This review aims to provide a comprehensive overview of the traditional uses, chemical and physical properties, and modern health applications of KGM. It highlights cutting-edge research, discusses challenges and limitations, and identifies future directions for advancing the utility of KGM in health and nutrition. KGM demonstrates remarkable health benefits, including improving metabolic health through weight management, blood glucose stabilization, and lipid profile enhancement. It also plays a vital role in gut health. Emerging evidence highlights its anti-inflammatory and immune-regulatory effects, with applications in managing inflammatory bowel disease, hyperthyroidism, and colorectal cancer (CRC). Recent advancements in multi-omics analyses and high-throughput screening (HTS) approaches have improved KGM extraction, characterization, and evaluation. However, potential side effects such as gastrointestinal discomfort and allergenicity, along with challenges in maintaining purity and molecular consistency, require careful consideration. KGM is a versatile dietary fiber with extensive applications in functional foods, nutraceuticals, and therapeutic interventions. Future research should focus on enhancing KGM's bioavailability, developing targeted delivery systems, and formulating novel applications.